Extraction of Staphyloxanthin from Staphylococcus aureus and Studying Some Biological Effect of Staphyloxanthin Pigment - Fatima Amer Abd Algabar (Journal of Global Pharma Technology, 2016)
Objective: This study aimed to extraction and purification of staphyloxanthine and to determine antibacterial effect of purified extract against pathogenic bacteria. Design and methods: To reach this goal from 306 samples of different clinical sources, Staphylococcus (22.8%) had been isolated and examined as S. aureus depending on cultural morphology, biochemical tests and Vitek2 system.  Staphyloxanthin pigment was extracted by using ethyl acetate with ethanol ,as wells the using qualitative and quantitative screening method to detect antibacterial effect of purified extract   then the results were statistically analyzed by SPSS to   perform the data analysis. Results: The results show significant difference in absorption of staphyloxanthin and the extracts; higher absorption of staphyloxanthin was recorded in tube 7 (0.998). Our study proved that purified extract of staphyloxanthin has an anti-bacterial effecting agent, It made inhibition zone against several kinds of gram negative bacteria at concentration (2, 20) mg/ml. This extract produces high inhibition zone (15mm) against Pseudomonas aeruginosa. In conclusion: our finding to confirm the ethyl acetate and ethanol method is very significant for extracting staphyloxanthin pigment. Our results indicate that column chromatography is one of the most important and widely used techniques for separation of pigment (staphylxanthin); also the purified extract of staphyloxanthin was established as anti-bacterial activity against several gram negative bacteria with highly inhibition zone against Pseudomonas aeruginosa. Keywords: Staphyloxanthin, Antibacterial, Purified extract, Well diffusion.